Spectrophotometric Estimation of Cefpirome Sulphate in Pharmaceutical Formulations - Vanitha Prakash, K.; Venkateswara Rao, J.; Appala Raju, N.; Himabindu, V. (Asian Journal of Chemistry, 2010)
Three simple, accurate, rapid and sensitive methods (A, B and C) have been developed for the estimation of cefpirome sulphate in its pharmaceutical dosage form. The method A and B are based on diazotization of primary amine group of cefpirome with sodium nitrite and hydrochloric acid followed by coupling with α-naphthylamine (method A) and N-(1-napthyl)ethylene diamine hydrochloride (method B) to form pink coloured chromogen with a characteristic absorption maxima at 512 nm and purple coloured chromogen exhibiting maximum absorption at 565 nm, respectively. The method C is based on the formation of red coloured chromogen with ferric chloride and 1,10-phenanthroline, which shows absorption maximum at 510 nm. The absorbance-concentration plot is linear over the range of 5-40 mcg/mL for method A, 2.5-20 mcg/ mL for method B and 2.5-40 mcg/mL for method C. Results of analysis for all the methods were validated statisti-cally and by recovery studies.